Implementing Deep Learning in Islamic Religious Education: Evidence from Indonesian Schools under the Merdeka Curriculum - Fadri, Irfal Khairul; Ummah, Khairatul; Munawaroh, Munawaroh; Hilmi, Hilmi; Musstanyah, Sman (FITRAH: International Islamic Education Journal, 2026)
The implementation of Deep Learning within Indonesia's Merdeka Curriculum has emerged as an important strategy for transforming teaching and learning. However, its application in Islamic Religious Education (IRE) at the elementary school level, particularly when integrated with school culture, remains underexplored. This study aims to analyze the implementation of the Deep Learning approach in IRE at SD Negeri 01 Sawahan, Padang City, focusing on: (1) the application of the principles of mindful learning, meaningful learning, and joyful learning; (2) implementation challenges; and (3) learning evaluation strategies. A qualitative case study design was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis involving 13 purposively selected participants, consisting of one principal, two IRE teachers, and ten students. Data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that the Deep Learning approach was implemented through collaborative group discussions, project-based learning, the use of digital learning media, and reflective learning activities. Its implementation was supported by the principles of mindful, meaningful, and joyful learning, although several challenges remained, including limited educational resources, diverse student characteristics, and the need to strengthen teachers' pedagogical competencies. The study also found that integrating the Deep Learning approach with the school's religious culture through the barcode-based Smart Surau program extended students' learning experiences beyond the classroom by fostering regular religious practices and authentic assessment, thereby reinforcing the internalization of Islamic values. These findings provide empirical evidence that the successful implementation of Deep Learning in IRE depends not only on classroom instructional strategies but also on a supportive school culture that functions as a pedagogical ecosystem for promoting meaningful learning experiences.